Individual Characteristics, Antibody, Work Environment and Sick Building Syndrome (SBS) - Ikmala, Riskita; Ma’rufi, Isa; Munawir, Al (Humanistic Network for Science and Technology (Address: Cemara street 25, Ds/Kec Sukorejo, Ponorogo, East Java, Indonesia 63453), 2018)
Sick Building Syndrome (SBS) is a collection of complaints that a person feels being inside of a building or a room. SBS happens to many employees who work indoors. The purpose of this study is to analyze the influence of individual characteristics, IgE antibodies, and work environment against the incidence of SBS in the employees of Telkom Jember. The research design used was case control. The results showed that there was influence of age, duration of work, IgE antibody, room temperature and humidity to the incidence of SBS on Telkom Jember employees with sig <0,05. The results also showed that smoking habits, nutritional status, ventilation conditions, lighting and room dust levels do not affect the occurrence of SBS. Improvements that can be done are improvements to the working environment, especially in controlling the temperature and humidity of the room and healthy living the for employees. Keywords: SBS, IgE, Work environment